2004
DOI: 10.1210/jc.2004-0571
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit and Hyperactivity Disorders in the Offspring of Mothers Exposed to Mild-Moderate Iodine Deficiency: A Possible Novel Iodine Deficiency Disorder in Developed Countries

Abstract: Over a period of almost 10 yr, we carried out a prospective study of the neuropsychological development of the offspring of 16 women from a moderately iodine-deficient area (area A) and of 11 control women from a marginally iodine-sufficient area (area B) whose thyroid function had been monitored during early gestation. Attention deficit and hyperactivity disorder (ADHD) was diagnosed in 11 of 16 area A children (68.7%) but in none from area B. Total intelligence quotient score was lower in area A than in area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
231
2
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(251 citation statements)
references
References 35 publications
6
231
2
12
Order By: Relevance
“…Based on the title screening, 850 records were eligible for abstract screening, of which 60 articles met the criteria for full article review. Following thorough review of the articles, 13 (26,27,28,29,30,31,32,33,34,35,36,37,38) remained eligible ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the title screening, 850 records were eligible for abstract screening, of which 60 articles met the criteria for full article review. Following thorough review of the articles, 13 (26,27,28,29,30,31,32,33,34,35,36,37,38) remained eligible ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…25,26 In the Generation R Study, 8-year-old children of women from an iodine-deficient geographic area who had been identified with hypothyroxinemia before 20 weeks of gestation were found to have higher ADHD index scores than children of women without hypothyroxinemia. 26 This association persisted after adjustment for IQ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence for the association between thyroid function and attention deficit/hyperactivity disorder (ADHD) (11)(12)(13). Previously, we reported that maternal thyroid dysfunction in early pregnancy predicted impaired cognition and attention deficit/hyperactivity problems in preschool children (14,15).…”
mentioning
confidence: 97%